(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Effective access control and revocation mechanisms are paramount in the ever-evolving landscape of information security. Traditional models often fall short in addressing the complexities of modern systems, necessitating the integration of context-aware decision-making and multi-granularity attributes. In this manuscript, we propose a novel access control framework leveraging the strengths of Attribute-Based Access Control (ABAC) and Attribute-Based Encryption (ABE) and blockchain technologies. The decentralized and immutable nature of blockchain further bolsters the trustworthiness of access control decisions. Our method introduces context-awareness and multi-granularity attributes into the decision-making process, enhancing adaptability and responsiveness. Through extensive experiments and comparisons with existing approaches, our results demonstrate the superior performance of our proposed method. This work not only contributes to the theoretical foundations of access control but also provides a practical solution that outperforms current state-of-the art methods, addressing the dynamic security challenges of contemporary information systems.